COMPREHENSIVE MDCT ANALYSIS OF RARE CORONARY AND NON-CORONARY ANOMALIES IN PEDIATRIC PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Aims and Objectives: to assess the spectrum of coronary and non-coronary artery anatomy and its various anomalies as depicted on CT angiography. Material and Method: A prospective observational study was conducted in department of Radiodiagnosis, KGMU, for one year duration. CT Angiography (CTA) was done in 64 SLICE MDCT SCANNER (PHILIPS BRILLIANCE, Netherland). Study included pediatric population (age 1 - 20 years) having complaints of acute chest pain and suspected coronary artery disease with or without equivocal findings in 2D ECHO. Patients with Allergy to iodinated contrast agents, Cardiac arrhythmias, Renal insufficiency (GFR